Social work and foster care - Cosis-Brown, Helen (Los Angeles : Learning Matters, 2014)
Working with children in foster care is a demanding and rigorous aspect of social work practice. Often difficult decisions have to be made and for students and practitioners alike, there is a vast array of legislation, law and social policy to understand. This book will help social workers and social work students get to grips with the complexity of foster care. The child is placed at the heart of the text and there are substantial chapters on law, policy frameworks and the overreaching theoretical and research evidence to support good practice.
A practical guide to social work with foster care.
Introduction The Legal and Policy Framework for Foster Care Recommendations Arising from Inquiry Reports and Serious Case Reviews (SCRs) Assessment of Prospective Foster Carers Supervision and Support of Foster Carers Foster Carer Development and Training Foster Carers Reviews Fostering Panels Conclusion
Includes bibliographical references and index.
Keywords: Foster home care -- United Kingdom; Foster children -- Services for -- United Kingdom